The Role of Bojonegoro Regency Baznas in Supporting Education Levels During the Covid 19 Pandemic In Bojonegoro - Sri Asih Wulandari; Sri Abidah Suryaningsih (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
This study aims to find out about the role of BAZNAS in Bojonegoro Regency in supporting education levels during the Covid-19 pandemic in Bojonegoro. The object of this research is BAZNAS, Bojonegoro Regency. This study uses a descriptive qualitative approach with data collection techniques used are documentation, interviews, and observations, while the data validity test techniques used are method triangulation and data source triangulation. The results of this study indicate that the role of BAZNAS in Bojonegoro Regency in supporting education through the scholarship assistance program is very helpful for scholarship recipients. With the scholarship assistance program, students and students are able to focus on the teaching and learning process without worrying about costs amidst the COVID-19 pandemic.